Maximizing Transfection Efficiency of Vertically Aligned Silicon Nanowire Arrays. (13th October 2015) - Elnathan, Roey; Delalat, Bahman; Brodoceanu, Daniel; Alhmoud, Hashim; Harding, Frances J.; Buehler, Katrin; Nelson, Adrienne; Isa, Lucio; Kraus, Tobias; Voelcker, Nicolas H.
Abstract : Vertically aligned silicon nanowire (VA‐SiNW) arrays are emerging as a powerful new tool for gene delivery by means of mechanical transfection. In order to utilize this tool efficiently, uncertainties around the required design parameters need to be removed. Here, a combination of nanosphere lithography and templated metal‐assisted wet chemical etching is used to fabricate VA‐SiNW arrays with a range of diameters, heights, and densities. This fabrication strategy allows identification of critical parameters of surface topography and consequently the design of SiNW arrays that deliver plasmid with high transfection efficiency into a diverse range of human cells whilst maintaining high cell viability. These results illuminate the cell‐materials interactions that mediate VA‐SiNW transfection and have the potential to transform gene therapy and underpin future treatment modalities. Abstract : An easy‐to‐implement approach to control geometrical parameters in vertically aligned silicon nanowire arrays —which are used in gene delivery by means of mechanical transfection—provided. This is realized by combining nanosphere lithography and templated metal‐assisted wet chemical etching. Optimized nanowire array configurations produce transfection efficiencies approaching 95%.